1983
DOI: 10.3758/bf03202936
|View full text |Cite
|
Sign up to set email alerts
|

Duration judgment and the experience of change

Abstract: Predictions based on storage size, processing effort, and change models of time estimation were tested in five experiments. The first of these presented subjects with stimulus patterns that varied on dimensions of sensory-event number and uncertainty. Subjects estimated the duration of time periods using the reproduction method. Duration estimates were most accurately predicted by the number of sensory events in each pattern. This relationship was generally positive, although the specific function relating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
68
2

Year Published

1985
1985
1998
1998

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 19 publications
4
68
2
Order By: Relevance
“…Moderate numbers of targets were related to longer temporal productions, but only for the 6-sec stationary displays. A similar pattern has been observed elsewhere (Poynter & Homa, 1983), and this effect will be considered in more detail in the general discussion section.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Moderate numbers of targets were related to longer temporal productions, but only for the 6-sec stationary displays. A similar pattern has been observed elsewhere (Poynter & Homa, 1983), and this effect will be considered in more detail in the general discussion section.…”
Section: Resultssupporting
confidence: 85%
“…An alternative approach, advanced by a number of theorists, emphasizes the role of stimulus change in time perception (e.g., Block, 1982Block, , 1990Fraisse, 1963Fraisse, , 1978Gibson, 1975;Poynter & Homa, 1983). According to this view, changes in stimulus events lengthen the experience of time because "change is the psychological index of time passage" (Poynter, 1989, p. 309).…”
mentioning
confidence: 99%
“…They observed, among other things, that a time interval seems to pass more slowly if it contains an unpleasant (as opposed to a pleasant) task, a task in which a person has little to do (as opposedto one in which the person is busy), a single task (as opposed to several different tasks), a task that takes place in an unchanging (as opposed to a changing) environment, and a task that is easy (as opposedto challenging). This correspondswell to results on actual duration judgments, indicatingthat intervals with unpleasant stimuli (e.g., Harton, 1939;Langer et al, 1961), many stimuli (e.g., Buffardi, 1971;Ornstein, 1969), variable .stimuli (e.g., Block & Reed, 1978;Poynter, 1983;Poynter & Homa, 1983), and difficult stimuli (e.g., Burnside, 1971;Hicks et al, 1976;Zakay, Nitzan, & Glicksohn, 1983) are judged to be longer than intervals with neutral or pleasant, few, less variable (i.e., more monotonous), and easy stimuli.…”
Section: Methodssupporting
confidence: 81%
“…Severalof these variables (facets) are related to judgments on the duration of intervals (Galinat, 1984): (1) numberof stimuliperceivedduring a given interval (e.g., Buffardi, 1971;Frankenhauser, 1959;Mo, 1971;Ornstein, 1969); (2) amount of memory space required to store the events (e.g., Mulligan & Schiffman, 1979;Ornstein, 1969;Schiffman& Bobko, 1974, 1977; (3) difficulty (i.e., processing demands of the stimuli) DURAnON BELIEFS 309 (e.g., Avant, Lyman, & Antes, 1975;Burnside, 1971;Hicks et al, 1976;Michon, 1965;Thomas & Weaver, 1975;Vroon, 1970); (4) variability (i.e., the number of perceived changes of the stimuli) (Block & Reed, 1978;Fraisse, 1963;Poynter, 1983;Poynter & Homa, 1983); (5) evaluation (i.e., the perceived pleasantnessof stimuli (e.g., Edmonds, Cahoon, & Bridges, 1981;Harton, 1939;Langer, Wapner, & Werner, 1%1;Rosenzweig& Koht, 1933); (6) degree of anticipatory tension toward the occurrence of an event (e.g., Block, George, & Reed, 1980;Lordahl & Berkowitz, 1975); (7) attentional selectivity during encoding and retrieving of the stimuli (Underwood, 1975;Underwood & Swain, 1973) or attentional focusing on the passage oftime itself (e.g., Curton & Lordahl, 1974;Fraisse, 1963;McKay, 1977). Other researchers have presented somewhat different lists of facets.…”
mentioning
confidence: 99%
“…These predictions were inspired by studies that have shown that increasing the amount of stimulus information within an interval while duration is held constant can strongly influence subjects' judgments of duration. Three major theories of these findings have emerged: the storage size model (Block, 1974;Mulligan & Schiffman, 1979;Ornstein, 1969), the processing effort model (Avant, Lyman, & Antes, 1975;Fraisse, 1979;Thomas & Weaver, 1975), and the change model (Block & Reed, 1978;Poynter & Homa, 1983). All these models posit that duration judgment is cognitively mediated.…”
Section: Methodsmentioning
confidence: 99%